The Chromosomal parDE2 Toxin–Antitoxin System of Mycobacterium tuberculosis H37Rv: Genetic and Functional Characterization - Gupta, Manish; Nayyar, Nishtha; Chawla, Meenakshi; Sitaraman, Ramakrishnan; Bhatnagar, Rakesh; Banerjee, Nirupama (Frontiers in Microbiology, 2016)
Mycobacterium tuberculosis H37Rv escapes host-generated stresses by entering a dormant persistent state. Activation of toxin-antitoxin modules is one of the mechanisms known to trigger such a state with low metabolic activity. M. tuberculosis harbours a large number of TA systems mostly located within discernible genomic islands. We have investigated the parDE2 operon of M. tuberculosis H37Rv encoding MParE2 toxin and MParD2 antitoxin proteins. The parDE2 locus was transcriptionally active from growth phase till late stationary phase in M. tuberculosis. A functional promoter located upstream of parD2 GTG start-site was identified by 5´-RACE and lacZ reporter assay. The MParD2 protein transcriptionally regulated the PparDE2 promoter by interacting through Arg16 and Ser15 residues located in the N-terminus. In E. coli, ectopic expression of MParE2 inhibited growth in early stages, with a drastic reduction in colony forming units. Live-dead analysis revealed that the reduction was not due to cell death alone but due to formation of viable but non-culturable cells (VBNCs) also. The toxic activity of the protein, identified in the C-terminal residues Glu98 and Arg102, was neutralized by the antitoxin MParD2, both in vivo and in vitro. MParE2 inhibited mycobacterial DNA gyrase and interacted with the GyrB subunit without affecting its ATPase activity. Introduction of parE2 gene in the heterologous M. smegmatis host prevented growth and colony formation by the transformed cells. An M. smegmatis strain containing the parDE2 operon also switched to a non-culturable phenotype in response to oxidative stress. Loss in colony-forming ability of a major part of the MParE2 expressing cells suggests its potential role in dormancy, a cellular strategy for adaptation to environmental stresses. Our study has laid the foundation for future investigations to explore the physiological significance of parDE2 operon in mycobacterial pathogenesis.